Efficiency assessment of induction motors drives operating under shaft misalignment conditions - Verucchi, Carlos (2020)
Historically, the negative effects of misalignment between the motor shaft and the load on the electric drives are well known. Vibrations, loss of life of couplings and deterioration of efficiency are some of these effects. Regarding this last point, the literature offers contradictory opinions. Some studies consider that the loss of efficiency in cases of misalignment is undesirable; while others consider that it has significant importance. In this paper, experimental results show in which cases the misalignment has a significant effect on efficiency and in which cases it can be neglected. For this, radial and angular misalignment cases are stud-ied with four of the most used flexible couplings in the industry. The obtained results are analysed in relation to the actual regulations on energy efficiency in induction motors. The reached conclusions offer new tools for the correct selection of flexible couplings tending to the improvement of energy efficiency.